Patterns and processes in plant phylogeography in the Mediterranean Basin. A review - Nieto Feliner, Gonzalo (Perspectives in plant ecology, evolution and systematics, 2014)
Phylogeography, born to bridge population genetics and phylogenetics in an explicit geographic context, has provided a successful platform for unveiling species evolutionary histories. The Mediterranean Basin, one of the earth's 25 biodiversity hotspots, is known for its complex geological and palaeoclimatic history. Aiming to throw light on the causes and circumstances that underlie such a rich biota, a review of the phylogeographic literature on plant lineages from the Mediterranean Basin is presented focusing on two levels. First, phylogeographic patterns are examined, arranged by potential driving forces such as longitude, latitude – and its interaction with altitude –, straits or glacial refugia. Spatial coincidences in phylogeographic splits are found but, in comparison to other regions such as the Alps or North America, no largely common phylogeographic patterns across species are found in this region. Factors contributing to phylogeographic complexity and scarcity of common patterns include less drastic effects of Pleistocene glaciations than other temperate regions, environmental heterogeneity, the blurring of genetic footprints via admixing over time and, for older lineages, possibly a greater stochasticity due to the accumulation of responses to palaeoclimatic changes. At a second level, processes inferred in phylogeographically framed studies that are potential drivers of evolution are examined. These include gradual range expansion, vicariance, long-distance dispersal, radiations, hybridization and introgression, changes in reproductive system, and determinants of successful colonization. Future phylogeographic studies have a great potential to help explaining biodiversity patterns of plant groups and understanding why the Basin has come to be one of the biodiversity hotspots on earth. This potential is based on the crucial questions that can be addressed when geographic gaps are adequately filled (mainly northern Africa and the eastern part of the region), on the important contribution of younger lineages – for which phylogeographic approaches are most useful – to the whole diversity of the Basin, and on the integration of new methods, particularly those that allow refining the search for spatio-temporal concordance across genealogies.